Impact of various dietary lipids on amelioration of biomarkers linked to metabolic syndrome in both healthy and diabetic Wistar rats - Weaam I. Abudigin; Adnan Bajaber; Pandurangan Subash-Babu (BMC Nutrition, 2024)
Abstract Background The present study was designed to investigate the influence of different dietary lipids (sheep’s fat, olive oil, coconut oil, and corn oil) on specific biomarkers associated with metabolic syndrome in both healthy and diabetic rats. Methods The study designed for 45 days, utilized a male diabetic wistar rat (body weight, 180–220 g) model induced by streptozotocin (45 mg/kg bw). The rats were divided into two sections: five non-diabetic and five diabetic groups, each containing six rats. The first group in each section serving as the control, received a standard diet. Both non-diabetic or diabetic groups, were provided with a standard diet enriched with 15% sheep fat, 15% coconut oil, 15% olive oil, and 15% corn oil, respectively for a duration of 45 days. Results Post-supplementation, both healthy and diabetic control rats exhibited a higher food intake compared to rats supplemented with lipid diet; notably food intake was higher in diabetic control than healthy control. However, rats fed with coconut oil, olive oil and sheep fat showed weight gain at the end of the experiment, in both healthy and diabetic groups. Coconut oil supplementation significantly (p ≤ 0.05) increased HDL-C and total cholesterol level in diabetic groups compared to healthy group, it was confirmed by an increased PPAR-α and ABCA-1 protein level. Olive oil significantly decreased triglyceride, total cholesterol, and LDL-C levels in diabetic rats when compared to sheep fat or coconut oil. Corn oil significantly decreased fasting glucose, total cholesterol and LDL-C levels compared to all other groups. Corn and olive oil supplemented normal groups, found with significant increase in hepatic glucose-lipid oxidative metabolism associated protein, like FGF-21, MSH, ABCA-1, PPAR-γ and decreased lipogenesis proteins like, SREBP and PPAR-α levels. In contrast, sheep grease and coconut oil increased SREBP and PPAR-α expression in both normal and diabetic groups. Most notably, normal and diabetic groups pretreated with sheep grease resulted in increased inflammatory (MCP-1, IL-1β, TLR-4, TNF-α), and oxidative stress markers (LPO, GSH, GPx, SOD and CAT) linked with metabolic complications. Conclusion The combination or alternative use of olive oil and corn oil in daily diet may play a significant role in preventing proinflammatory condition associated with insulin resistance and cardiovascular diseases.